Trans-aesthetics of Baudrillard: Simulacrum and art in an Epoch of Total Sham - Vaskes Santches, Irina (Estudios de Filosofía, 2008)
This article describes simulacrum, a principal notion of Jean Baudrillard. Defining present simulacrum as the most fundamental extermination of illusion, the author claims the total disillusion that tends to disappear reality and to destroy referential and significant representation. With total simulation, Art and Aesthetics go through the transaesthetic period when exceeding themselves they have been losing their own purpose and specificity. From aesthetic and artistic approach to simulacrum, various models of artistic simulation are presented, and their consequences for art are analyzed, which present state is considered by Baudrillard as conspiracy of the art.